PENGARUH PENGELOLAAN BARANG MILIK DAERAH TERHADAP PENGAMANAN ASET - Migel A. Pitay; Jennie S. Sir; Meyulinda Aviana Elim (JAKA - Jurnal Jurusan Akuntasi, 2019)
This study aimed to test the Effect of Regional Property Management Security Against Assets In BAPPELITBANGDA NTT. The sampling method used by the author is simple random sampling. The type of data that is used by the author is the primary data used in this study was obtained from questionnaires distributed to 20 respondents who met the criteria of the sample. Dependent and independent variables used in this study is the variable with the ordinal scale. The research model used by the author is to use statistical analysis Simple Linear Regression equations. The results showed that the asset management area to safeguard assets and significant positive effect on the value of determination coefficient of 34.322 or, while the influence of other variables to securing assets reached 0.296 % of these results shows that although the asset management area of influence a positive and significant impact on the assets securing the area . In other words, the success of efforts to secure the assets in BAPPELITBANGDA NTT determined more by factors other than the management of assets that have been done so far